Studi Pemanfaatan Idle Capacity Instalasi Pengolahan Lumpur Tinja (IPLT) Keputih Surabaya - Nurhayati, Ervin; Arseto Yekti Bagastyo; Cynthia Dyah Puspitasari; Joko Pramono; Fathyah, Fathyah; Rahayu, Dewi Puji; Subechi, Dya Nur Mangzila (Teknik Lingkungan Universitas Islam Indonesia, 2024)
IPLT Keputih, the only fecal sludge treatment plant in Surabaya City, plays a critical role in the city's sanitation infrastructure. Its operation is critical to manage the fecal sludge generated by Surabaya residents, ensuring that the effluent is effectively treated before being safely discharged to the environment. According to previous studies, IPLT Keputih still has significant untapped potential, especially in the Solid Separation Chamber (SSC) and Grease Trap (GT) units, which have idle capacity that can be optimized to improve overall efficiency. The study involved primary and secondary data collection. Primary data was collected through comprehensive field observations and measurements, while secondary data was obtained from relevant agencies. Data analysis showed that IPLT Keputih currently treats an average of 97.71 m3 of septage per day. However, the facility has an idle capacity of 139.89 m3/day, which indicates a great opportunity to improve utilization. The calculation of the existing idle capacity was conducted based on the maximum discharge of sludge entering the IPLT Keputih in 2022. Several scenarios were developed to fully utilize the idle capacity of the SSC and GT units. The scenarios include the optimization of the SSC unit through improved desludging services, the optimization of the SSC and GT through improved non-fecal sludge management services for restaurants, as well as the implementation of a blended approach to improve the overall service of IPLT Keputih.